ONTOLOGICAL MODEL OF INFORMATION SYSTEM ARCHITECTURE, BASED ON SERVICE APPROACH - Ievlanov, M. V. (Radio Electronics, Computer Science, Control, 2013)
The article describes the concept of modern ideas of «architecture», which are used in the development of information systems for different purposes. The features of the service approach to the representation of the information system are considered. Proposed refinement of the concept of «architecture of IT services» and «architecture of IT services». Visual models of the relationship major elements for the concepts «service approach to the development of information systems» and «information system architecture» are developed.